2010
DOI: 10.1177/1557085110376341
|View full text |Cite
|
Sign up to set email alerts
|

Looking in the Rearview Mirror: What Incarcerated Women Think Girls Need From The System

Abstract: Until the 1980s, scant literature existed about the programmatic needs of delinquent girls. Girls are being introduced into the system at a faster rate than in the past, and the number of girls arrested for "serious" crimes has increased; therefore, genderspecific needs can no longer be overlooked. Much of the gender-specific knowledge focuses on risk and protective factors, though the literature on girls' programmatic needs is beginning to grow. This study attempts to ascertain what girls need from the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Our emphasis on providing the survivors with this platform to voice their suggestions is due to the fact that previous literature assesses the quality of the treatment as generally low, and programs as ineffective. It is posited that for treatment to be effective, it must be gendered (i.e., take into account the specific needs of different genders; see, for example, Garcia & Lane, 2010). The treatment of sexually exploited juveniles must take into account the complex and often tragic histories of this population that in many cases involve abuse, neglect, and otherwise unstable backgrounds (Chesney-Lind, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Our emphasis on providing the survivors with this platform to voice their suggestions is due to the fact that previous literature assesses the quality of the treatment as generally low, and programs as ineffective. It is posited that for treatment to be effective, it must be gendered (i.e., take into account the specific needs of different genders; see, for example, Garcia & Lane, 2010). The treatment of sexually exploited juveniles must take into account the complex and often tragic histories of this population that in many cases involve abuse, neglect, and otherwise unstable backgrounds (Chesney-Lind, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Gender responsivity can be seen as a paradigm for addressing girls’ unique needs in the juvenile justice system. Gender responsivity refers to a comprehensive systems response to female delinquency that emphasizes the importance of girls’ experiences as well as addresses girls’ unique psychological, developmental and social needs, and pathways into crime (Garcia & Lane, 2010). In essence, programming that is effective for girls involved in the juvenile justice system should be specifically designed and targeted for their unique, gender-based needs.…”
Section: Gender-responsive Policy Reformmentioning
confidence: 99%
“…In a recent study, Garcia and Lane (2010) asked incarcerated women to reflect back on their experiences in juvenile correctional facilities, and the women had strong ideas and recommendations for how to improve the treatment of incarcerated girls. They suggested that female staff and role models are important for girls in the system.…”
Section: Recent Research and Trendsmentioning
confidence: 99%
“…They suggested that female staff and role models are important for girls in the system. Along with female mentors, they recommended parenting classes with self‐esteem building components, and individualized counseling to help the girls get over abusive histories (Garcia and Lane 2010). Research that gives voice to the growing population of girls in juvenile correctional facilities may help to create, assess, and direct successful gender‐specific programs.…”
Section: Recent Research and Trendsmentioning
confidence: 99%